UNIFIED DATA PROCESSING SYSTEM DEVELOPMENT FOR AN EXPRESS LASER EXAMINATION - L. V. Rudikova (Системный анализ и прикладная информатика)
The article describes general approach to the creation of an universal Internetsystem, which is designed for the collection, storage and processing of data, which related with an express laser examination. The system is based on client server architecture. The user interface is implemented as a webpage. The system allows storing and processing results of examination of works of art and related data.